2001
DOI: 10.1001/jama.285.13.1711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atorvastatin on Early Recurrent Ischemic Events in Acute Coronary Syndromes<SUBTITLE>The MIRACL Study: A Randomized Controlled Trial</SUBTITLE>

Abstract: For patients with acute coronary syndrome, lipid-lowering therapy with atorvastatin, 80 mg/d, reduces recurrent ischemic events in the first 16 weeks, mostly recurrent symptomatic ischemia requiring rehospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
259
2
18

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,181 publications
(305 citation statements)
references
References 19 publications
6
259
2
18
Order By: Relevance
“…FMDand IMT at baseline and at six monthswere4. 1 Major adverse cardiovasculare vents occurredi n 2.1% in the atorvastatingroup and 1.9% in the control group (p= 0.61). In conclusion, in this pilott riala ggressive lipid-lowering with 80 mg of atorvastatindailyfor six monthshad no effect on brachial artery FMD in patients with PAD.…”
Section: Discussionmentioning
confidence: 96%
“…FMDand IMT at baseline and at six monthswere4. 1 Major adverse cardiovasculare vents occurredi n 2.1% in the atorvastatingroup and 1.9% in the control group (p= 0.61). In conclusion, in this pilott riala ggressive lipid-lowering with 80 mg of atorvastatindailyfor six monthshad no effect on brachial artery FMD in patients with PAD.…”
Section: Discussionmentioning
confidence: 96%
“…High‐intensity statin therapy has been shown in several randomized trials20, 21, 22, 23 to be superior to moderate‐intensity statin in further reducing major cardiovascular events, and a recent report from observational data has shown a survival benefit of high‐intensity statin over submaximal statin therapy. Adherence to guideline recommendation to use high‐intensity statins rather than moderate‐intensity statin among our cohort could potentially prevent >1800 cardiovascular events over a 10‐year period.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have shown reduction of IR-injury as a result of statin treatment in both the heart and the kidney [14][15][16][17] . This putative protection may explain the clinical observation that early initiation of statin treatment in patients with an acute cardiovascular event improves long-term prognosis as compared with a delayed start of this treatment [18][19][20] . Furthermore in two randomised clinical trials one day treatment with…”
Section: Introductionmentioning
confidence: 99%